Novel surgical management of tibialis anterior tendinosis using an anchor augment - Naude, Jaco; Saragas, Nikiforos Pandelis; Ferrao, Paulo Norberto Faria (Journal of the Foot & Ankle, 2023)
Objective: The objective of this paper was to describe a surgical technique for the management of TA tendinosis: Debridement, repair, and augmentation with a suture anchor without tendon transfer. Methods: This is a retrospective case series including five patients managed surgically for TA tendinosis. If ≥ 30% of healthy tendon remains after debridement, the tendon is augmented with a suture anchor, with the suture incorporating the healthy tendon as a checkrein. Patient outcomes were assessed using the AOFAS midfoot, VAS Pain, and SEFAS score. Results: The mean AOFAS improved preoperatively from 37.0 (range 18–51) to 97.6 (range 95–100), the VAS pain score from 8.0 (range 7–9) to 0.8 (range 0–1), and the mean SEFAS score at final follow-up was 43.8 (range 41–48). Conclusions: Tibialis anterior tendinosis is an uncommon degenerative process. Early diagnosis and appropriate management can prevent tendon rupture. This case series of debridement, repair, and augmentation with a suture anchor showed high patient satisfaction and good clinical outcomes without needing a tendon transfer. Level of Evidence III; Therapeutic Studies - Investigating the Results of Treatment; Retrospective Comparative Study